Cells with haematopoietic stem cell phenotype in adult human endometrium: relevance to infertility? - O'FARRELLY, CLIONA; LYNCH, LYDIA (My University, 2007)
BACKGROUND: Uterine lymphoid cell repertoires are specialized in order to meet the twin demands of successful pregnancy and local immunosurveillance. The possibility that some of these populations might differentiate locally from progenitor cells has been proposed. METHODS: Endometrial tissue from women with a history of infertility as well as fertile controls was examined for haematopoietic stem cells (HSCs) and lymphoid progenitors using three-colour flow cytometry. RESULTS: Significant populations of phenotypic HSCs (CD34+ CD45+ ) were detected in all samples, a high proportion of which co-expressed the differentiation marker CD45RA (45.7%), indicating ongoing differentiation. Almost 30% of uterine HSCs co-expressed CD56 and 44% co-expressed CD7, suggesting the presence of lymphoid progenitors. Small proportions expressed CD127 and CD122, receptors for interleukin (IL)-7 and IL-15, respectively. HSC numbers were similar in the endometrial samples from fertile and infertile women. However, the proportion co-expressing the natural killer (NK) antigen CD56 was significantly increased compared with HSCs found in the endometrium of fertile controls (P = 0.002). CONCLUSIONS: This is the first demonstration of cells with an HSC phenotype in the human endometrium, and increased proportions of NK progenitors in endometrium of women with infertility suggests a dysregulation of this pathway that may contribute to infertility.
PUBLISHED
Keywords: Uterine lymphoid cell repertoires; Uterine lymphoid cell repertoires; Immunology, Inflammation & Infection